Design and analysis ergonomics workstation in stamping industry - Seri Rahayu , Kamat; Mohamad Firdaus , Ain (2014)
Nowadays, in manufacturing industries field the competition are more intense and more competitor try won the heart of their customers. Hence, the demands for the product increase and the company need to fulfill the demand. As the demands increases, the company should produce more product than usual. In the same time the welfare and health of the workers should be consider. Some factors such as workstation design should taken into consideration in order to increase the productivity and at the same time protect workers from any hazard, injuries and health problem such as Musculoskeletal Disorder (MSD). Therefore, the workstations need to be redesign by applying the ergonomics principles to reduce the risks of MSD. In order to improve and redesign workstation, Rapid Upper Limb Assessment (RULA) Analysis that available in CATIA software is used to analyze and evaluate the working posture of the workers. The anthropometry of the workers and the workspace design measurement data were used in RULA Analysis. The RULA scores and action level is determined to indicates the working posture. Besides, the assessment of manual lifting – National Institute for Occupational Safety and Health (NIOSH) Approach is used to recognized and addressed the problem of work related back injuries and has formulated the equation for lifting tasks. The productivity of the company before and after improvement is calculated using mathematical equations. After redesign the workstation, the RULA scores of the worker’s working postures improved.